Effects of enzyme supplementation on diets of medium-heavy laying hens at 28 to 40 weeks - Resende, Vanessa Cristina; Brainer, Mônica Maria; Modesto, Karla; Leite, Paulo Ricardo; Freitas, Paulo Vítor (Revista Ciência Agronômica, 2017)
The aim of this study was to verify the effect of the addition of an enzyme complex on performance (feed intake, egg production, egg weight and egg mass, feed conversion per egg mass, and feed conversion per dozen eggs), and on egg quality (% of shell, albumen and yolk, shell thickness, specific gravity, Haugh unit, yolk index, and albumen index), in medium-heavy laying hens at 28 to 40 weeks of age. A total of 240 Hy-Line Brown laying hens were used in a randomised block design with 10 replications of six birds per lot and four treatments: positive control (basal feed), negative control (with a reduction in metabolisable energy, crude protein, calcium and phosphorus), negative control + enzymes, and positive control + enzymes. The enzyme complex, composed of β-glucanases, β-xylanase, cellulase and phytase, was added to the feed at a ratio of 50 g t-1. The data were submitted to analysis of variance with the mean values compared by Tukey’s test at 5%. There was no difference in feed intake or egg weight between treatments. However, the addition of the enzyme complex to the negative control diet gave results similar to the remaining performance variables when compared to the positive control group. For the external and internal quality of the eggs, there was no difference between treatments for the variables under evaluation, except for the albumin index. It was concluded that use of the enzyme complex in the diet of medium-heavy laying hens gives a reduction in nutritional density without compromising production performance or egg quality.